Myostatin in the placentae of pregnancies complicated with gestational diabetes mellitus. Issue 1 (January 2015) - Peiris, H.N.; Lappas, M.; Georgiou, H.M.; Vaswani, K.; Salomon, C.; Rice, G.E.; Mitchell, M.D.
Abstract: Introduction: Gestational diabetes mellitus (GDM) is characterised by maternal glucose intolerance and insulin resistance during pregnancy. Myostatin, initially identified as a negative regulator of muscle development may also function in the regulation of placental development and glucose uptake. Myostatin expression in placentae of GDM complicated pregnancies is unknown. However, higher myostatin levels occur in placentae of pregnancies complicated with preeclampsia. We hypothesise that myostatin will be differentially expressed in GDM complicated pregnancies. Methods: Myostatin concentrations (ELISA) were evaluated in plasma of presymptomatic women who later developed GDM and compared to plasma of normal glucose tolerant (NGT) women. Furthermore, myostatin protein expression (Western blot) was studied in placentae of pregnant women with GDM (treated with diet or insulin) compared to placentae of NGT women. Results: No significant difference in myostatin concentration was seen in plasma of pre-symptomatic GDM women compared to NGT women. In placenta significant differences in myostatin protein expressions (higher precursor; p  < 0.05and lower dimer: p  < 0.005) were observed in GDM complicated compared to NGT pregnancies. Furthermore, placentae of GDM women treated with insulin compared to diet have higher dimer ( p  < 0.005) and lower precursor ( p  < 0.05). Compared to lean women, placentae of obese NGT women were lower in myostatin dimer expression ( p  < 0.05). Discussion: Myostatin expression in placental tissue is altered under stress conditions (e.g. obesity and abnormal glucose metabolism) found in pregnancies complicated with GDM. We hypothesise that myostatin is active in these placentae and could affect glucose homoeostasis and/or cytokine production thereby altering the function of the placenta. Highlights: Plasma concentrations of myostatin were evaluated in NGT and pre-symptomatic GDM women. Myostatin protein levels were evaluated in placentae of women with GDM and NGT pregnancies. No difference was seen in myostatin concentrations in plasma of NGT or pre-symptomatic GDM women. Myostatin protein expression is altered in placentae of women with GDM compared to NGT placentae. Placentae of diet and insulin treated women with GDM differentially expressed myostatin protein.